A simple feed orthogonal excitation X-band dual circular polarized microstrip patch array antenna - Das, Debprosad; Hossain, Md. Farhad; Hossain, Md. Azad (International Journal of Electrical and Computer Engineering (IJECE), 2024)
This work represents a microstrip patch array antenna which is designed and analyzed for the application of circular polarization in X band frequency range. The proposed antenna array has a very simple microstrip line feeding mechanism and each patch is energized orthogonally to acquire circular polarization without the need for any phase shifters. The array antenna has a slot line in the ground to electrically couple the signals from the microstrip feed line to feed each patch. The outcome demonstrates that the antenna is capable of radiating both left-hand circular polarization (LHCP) and right-hand circular polarization (RHCP). The designed work has a return loss of -41.88 dB, that is the antenna is perfectly matched. The outcome also demonstrates the antenna’s strong gain and directivity capabilities, which are 12.87 dBi and 13.30 dBi, respectively. The antenna resonates circularly at a frequency of 10 GHz.